2013
DOI: 10.1186/1471-2261-13-119
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-brachial index and the incidence of cardiovascular events in the Mediterranean low cardiovascular risk population ARTPER cohort

Abstract: BackgroundPeripheral arterial disease (PAD) of the lower limbs is a cardiovascular disease highly prevalent particularly in the asymptomatic form. Its prevalence starts to be a concern in low coronary risk countries like Spain. Few studies have analyzed the relationship between ankle-brachial index (ABI) and cardiovascular morbi-mortality in low cardiovascular risk countries like Spain where we observe significant low incidence of ischemic heart diseases together with high prevalence of cardiovascular risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
(36 reference statements)
4
31
0
3
Order By: Relevance
“…We found a strong association between pathological ABI and CHD and CVD events incidence (HR ¼ 2.46 and 2.64, respectively), similar to that reported in the ABI Collaboration Meta-analysis (HR ¼ 2.97 in men and 3.05 in women, for major coronary events) [16], which included 16 population cohort studies and more than 48,000 individuals. This association also has been reported in Mediterranean populations [15,35], with a magnitude of association similar to that observed in our study.…”
Section: Modelsupporting
confidence: 92%
“…We found a strong association between pathological ABI and CHD and CVD events incidence (HR ¼ 2.46 and 2.64, respectively), similar to that reported in the ABI Collaboration Meta-analysis (HR ¼ 2.97 in men and 3.05 in women, for major coronary events) [16], which included 16 population cohort studies and more than 48,000 individuals. This association also has been reported in Mediterranean populations [15,35], with a magnitude of association similar to that observed in our study.…”
Section: Modelsupporting
confidence: 92%
“…Several studies have shown that pulse wave velocity (PWV), a noninvasive clinical index of arterial stiffness, predicts cardiovascular events and all-cause mortality [38]. Prevention and early detection of arterial stiffness need to be promoted to avoid severe cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…The ABI is helpful for determining the arterial conditions linked to the lower limbs (i.e., the existence of peripheral arterial disease) 25) , and is a predictor of CVD events 26) . Even when the ABI level is 0.9 (as in our study subjects), the ABI measurement is useful for predicting the development of CVD 26) .…”
Section: Discussionmentioning
confidence: 99%